Inclusion of Students with ADHD in Secondary School Through an Innovative Motor Science Educational Curriculum - Domenico Tafuri; Davide Di Palma (Education Sciences)
This experimental study evaluated the effectiveness of an innovative motor science teaching program aimed at promoting the inclusion and involvement of students with Attention Deficit/Hyperactivity Disorder (ADHD) in secondary school. Sixty students (30 in the sample group and 30 in the control group) participated in the program, while 10 specially trained motor education teachers implemented the activities. The quantitative analysis showed a significant improvement in school inclusion scores (as measured by the Ainscow Inclusion Scale) and school engagement scores (Student Engagement Scale), with a strong positive correlation between the two parameters (r = 0.62, p < 0.01). The qualitative analysis, based on interviews with teachers, revealed positive perceptions of the program and emphasized the importance of training to address behavioral difficulties and ensure an inclusive school environment. The results suggest that customized motor education programs, combined with targeted training for teachers, can foster greater inclusion of students with ADHD in the school setting.